Communication and workflow barriers to family history collection among Spanish-speaking patients: Presenter(s): Kimberly Kaphingst, University of Utah, United States. (April 2023) - Liebermann, Erica; Taber, Peter; Vega, Alexis S
Abstract : Background: Family history is an important tool in primary care for assessing disease risk and tailoring recommendations regarding screening, surveillance, and genetic services referral. Previous studies have identified time pressure, inadequate staff/provider training, and limited patient knowledge as common barriers to family history collection. However, prior research on barriers to collecting family history among patients who speak a language other than English is limited. This study explored factors affecting the collection of family history information, generally and for cancer, for Spanish-speaking primary care patients. Methods: This qualitative study was conducted in two large U.S. healthcare systems in Utah and New York. We conducted 28 semi-structured interviews with medical assistants, physicians, and interpreters with experience collecting family history information for Spanish-speaking patients in these settings. Interview transcripts were coded using Dedoose qualitative software through an iterative process based on emergent Findings: and extensive discussion and consensus-building. Findings: The most common patient-level barrier to family history collection was the perception that some Spanish-speaking patients had limited knowledge of family history due to physical distance from family, cultural taboos, and limited health literacy. Interpersonal communication barriers related to the complexities of communicating with Spanish-speaking patients due to regional dialect and cultural differences and decisions about using formal interpreters (in-person or virtual) vs. clinic staff with varying levels of Spanish fluency. Organizational barriers included time pressures that were exacerbated by issues related to requesting and using interpreters, and ad hoc workflow adaptations for Spanish-speaking patients that might leave gaps in family history collection. Discussion: This study identified multi-level barriers to family history collection with Spanish-speaking patients in primary care. Findings: suggest that a key priority to enhance communication with Spanish-speaking patients would be to standardize processes for working with interpreters.